Supply Chain Management of Mango (Mangifera indica L.) Fruit: A Review With a Focus on Product Quality During Postharvest - Le, Truong Dang; Viet Nguyen, Thanh; Muoi, Nguyen Van; Toan, Ha Thanh; Lan, Nguyen Mai; Pham, Tri Nhut (Frontiers in Sustainable Food Systems, 2022)
Mango (Mangifera indica L.) is a widely consumed fruit in tropical/subtropical regions around the world due to its excellent flavor and taste, and valuable source of nutrients and phytochemical compounds. As a climacteric fruit, mango is easily perishable after harvesting due to the ripening process, environmental conditions, and improper postharvest handling, leading to significant quality losses as well as economic loss throughout a supply chain. Postharvest losses are attributed to harvesting at an improper maturity stage, poor postharvest pretreatment, improper packing and packaging, inappropriate storage temperature and distribution conditions. These caused mechanical damage, sap burn, spongy tissue, weight loss, fruit softening, decay, chilling injury, and postharvest diseases. Currently, each step in the supply chain has been applied many postharvest technologies to reduce the quality losses of mango fruits as well as improving their marketability with the highest retention of quality. This review documented available possible causes for the quality losses and observed the physicochemical changes of mango fruit when applying postharvest technologies at each critical step in the mango supply chain from harvesting, pre-treatment, packaging, storage, to distribution. The summarized information is expected to provide comprehensive quality changes of mango fruits and point out the proper technology at each step of the supply chain.